STUDI DESKRIPTIF TENTANG KTSP DALAM MATA PELAJARAN SEJARAH DI SMA NURUL FALAH PEKANBARU - Oemar, Kamaruddin (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
The problem is, how teachersâ understanding of the SBC in history lessons in classXI IPS SMA Nurul Falah Pekanbaru, and readiness to implement SBC history teacher in highschool Nurul Falah Pekanbaru. Nonetheless, for those who are not ready to use the model SBCmade MONE or developed by other schools, and adapt to the characteristics of each school, butwe also need to know the nature of the SBC.Formulation of the problem in order to study more clearly. based on the background of theproblem and disclosure issues noted above, the issues discussed in this research is âHow DescriptiveStudy of SBC in subjects at high school history Nurul Falah Pekanbaru Cityâ.Keywords: Implementation of the SBC, subject teachers of history.